(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
Higher education is crucial for successful development any country, and depending on changes in political and economic foundations in the country, the system might be reformed. However, despite this, many European countries from one point of view are similar in their teaching principles, while having some extent differences from another point. An example of such countries are Italy and Germany with their own characteristics, which are presented by us in this article. Having examined the higher education systems of Italy and Germany, we clearly stressed similarities and differences of management, financing and structures of higher education systems of these two countries. As a result, the study revealed that the management of educational systems in Italy and Germany carried out by the central government bodies (in Italy - Ministry of Education, Universities and Science, in Germany - Ministry of Education and Culture), as well as regional and local government (university). In Italy and Germany, the general standard rules are established for admission to the university for students who successfully complete high school graduation classes. Unlike Italy, where Lyceum with a Diploma di maturita is a middle school, in Germany, universities accept graduates of gymnasiums or general schools based on the program of the gymnasium that provides a document on secondary education – diploma ABITUR. An integral part of higher education both in Germany and Italy is the developed credit system and free academy. Unlike Italy, where the main part of the financing system of higher education is carried out by the central governing body, namely Ministry of Education, Universities and Science, in Germany, Higher education financing is mainly provided by local governing bodies. Universities in both countries- Italy and Germany, admitted a number of citizens from other countries who study here free or with a small fee. If Italy’s higher education system uses a 30-point grading system, Germany relies on 6 point one. Higher education in both Italy and Germany is based on 3-step system universities corresponding to the Bologna process, distinguished by the names of its degrees. Thus, the progressive development of higher education systems in Italy and Germany with their constant modernization leads to a successful resolution of problems associated with the management of higher education. The tables above provide a comparative analysis of external and internal governing bodies, financing in Italy and Germany, structures of their higher education, as well as grading systems and requirements for admission to universities in these countries.